Research of the Influence of Solid Particle on Elastohydrodynamic Lubrication of Spur Gear under Oscillation Condition - Huang Xingbao; Wang Youqiang; Liu Qian; Dong Ning (Jixie chuandong)
Considering solid particle,the elastohydrodynamic lubrication model of spur gear under oscillation condition is set up. The influences of solid particle on elastohydrodynamic lubrication of spur gear under sine law oscillation condition are studied,taking time- variant effect into account. The influence of a single solid particle,solid particles distribution density and solid particles speeds on oil film pressure and film thickness are analyzed. The results show that,the oil film pressure and film thickness under oscillation condition are in the cases of a similar double hump shape distribution. Considering solid particles centre film pressure and the maximum film pressure vary little,but centre film thickness and the minimum film thickness decrease remarkably. The greater solid particle distribution density is,the larger centre film pressure and the maximum film pressure are. The greater solid particles distribution density is,the thinner centre film thickness and the minimum film thickness are. The solid particles make evident differences to the minimum film thickness,if speed of solid particles is high,the minimum film thickness diminishes dramatically.